2003
DOI: 10.1080/1028602031000066852
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of IL-8 gene transcription by resveratrol in phorbol ester treated human monocytic cells

Abstract: Resveratrol (3,4',5-trihydroxy-trans-silbene), a natural phytoalexin found in grapes and other food products, has promising anti-inflammatory and anticancer effects. To observe the modulation of interleukin-8 (IL-8) production in human monocytic cells by resveratrol and explore its mechanism at the gene transcription level, U937 cells were stimulated with phorbol 12-myristate 13-acetate (PMA) for 24h. IL-8 protein in supernatants was measured by radioimmunoassay. The cytotoxicity of PMA, dexamethasone and resv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…other studies have revealed that resveratrol could inhibit IL-8 protein production induced by phorbol ester in human monocytic cells [29], and significantly decrease endothelin-1 and E-selectin mRNA expressions in high glucose cultured primary HUVECs [30]. In the present study, we also found that pretreatment with resveratrol attenuated CD40 expression induced by TNF-α in CRL-1730 endothelial cells.…”
Section: Discussionsupporting
confidence: 74%
“…other studies have revealed that resveratrol could inhibit IL-8 protein production induced by phorbol ester in human monocytic cells [29], and significantly decrease endothelin-1 and E-selectin mRNA expressions in high glucose cultured primary HUVECs [30]. In the present study, we also found that pretreatment with resveratrol attenuated CD40 expression induced by TNF-α in CRL-1730 endothelial cells.…”
Section: Discussionsupporting
confidence: 74%
“…Various reports have demonstrated that eukaryotic transcription factor such as AP-1 or NFκB are involved in the regulation of COX-2. Resveratrol is able to reduce the DNA binding activity and transcriptional activities of nuclear factors [81,107,108] and subsequently decreases the transcriptional activity of COX-2 expression [106,109]. These results are also shown in vivo where administration of resveratrol is able to suppress NMBA-induced rat oesophageal tumorigenesis by targeting COXs and PGs production [58].…”
Section: C) Resveratrol Chemoprevention By Inhibition Of Lipid Mediatorssupporting
confidence: 61%
“…Resveratrol inhibits the lipopolysaccharide (LPS)-induced expression of IL-1mRNA in monocytes and ECs [56]. Concerning IL-8, the gene transcription as well as the protein production are inhibited by resveratrol [57].…”
Section: Resveratrol and Foam Cell Formationmentioning
confidence: 99%